Retraction Note: Effects of Panax notoginseng saponins on severe acute pancreatitis through the regulation of mTOR/Akt and caspase-3 signaling pathway by upregulating miR-181b expression in rats - Ming-wei Liu; Rui Wei; Mei-xian Su; Hui Li; Tian-wen Fang; Wei Zhang (BMC Complementary Medicine and Therapies, 2022)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12906-018-2118-8.